Physical Exercise as an Adjunct Therapy in Schizophrenia: A Scoping Review of Its Effectiveness in Symptom Reduction - Widianti, Efri; Rosada, Amilia; Lufita Sari, Astri; Aulia Ma’rifa, Dzulfia; Ramadhany, Agfa; Ibrahim, Diq Diq; Susanti, Icih; Kusumah, Indra; Khoerunnisa, Khoerunnisa; Yasma Chaimira, Sausandha; Yahya Khalid Hamed, Fares (Media Karya Kesehatan, 2026)
Schizophrenia is a mental disorder that causes individuals to become physiologically and socially dysfunctional. Physical exercise is one of the non-pharmacological therapies that can be applied to patients with schizophrenia, offering advantages such as ease of implementation, wide applicability, and lower costs, making it a feasible option for widespread use. This study aims to determine the effectiveness of physical exercise interventions in reducing signs and symptoms in patients with schizophrenia. This study used a rapid review design, with articles collected from three databases: PubMed, EBSCO, and Scopus. Article selection was conducted based on predefined inclusion and exclusion criteria, resulting in seven eligible studies. Data analysis was performed by organizing the findings into a data extraction table to facilitate interpretation. The results indicate that physical exercise interventions are effective in reducing signs and symptoms of schizophrenia. The types of physical activities identified across the studies include cycling, yoga, treadmill walking, and aerobic exercises. In conclusion, in addition to antipsychotic medications used to manage symptoms, non-pharmacological interventions such as regular and structured physical exercise can help reduce symptoms and improve the quality of life in patients with schizophrenia.Keywords: Adjunct therapy, physical exercise, schizophrenia, scoping review, symptom reduction.